THE LOW MOTIVATED FACTORS IN EXTENSIVE READING ACHIEVEMENT - Nurhadi, Kardi; Larasaty, Gina (Research And Innovation In Language Learning (RILL), 2018)
The purpose of this study is to explain what are low motivated factors  in extensive reading achievement. It is based on the problems that some students had a low motivation in extensive reading, and they had a problem with their motivation. The bad effect of that problems the students are lazy to read in or out of the classroom. To achieve the purpose of study, the writer used case study with the design descriptive case study. The research participants took from the students from the second semester who took the extensive reading class at English Department University of Wiralodra Indramayu. To get the data, the writer used questionnaire, observation and interview. The findings showed that there was an equal percentage 21 % who said that reading ability and attitudes toward reading as the factors made them low motivated in extensive reading. In line the findings, Day and Bamford (1998: 29) revealed that low level reading abilities would normally lower expectations of success and thus lower motivation to read. And then,26 % of students said that sociocultural environment made them low motivate in extensive reading. The last, the highest percentage was 32 % who said that materials made the students low motivated in extensive reading. Regarding the research findings, the lecturer should create an interesting and meaningful materials to increase students motivation and achievement in extensive reading.